Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I know that it can be also evaluate using Taylor expansion, but I am intentionally want to solve it using L'Hôpital's rule:

$$ \lim\limits_{x\to 0} \frac{\sin x}{x}^{\frac{1}{1-\cos x}} = \lim\limits_{x\to 0}\exp\left( \frac{\ln(\frac{\sin x}{x})}{1-\cos x} \right)$$

Now, from continuity and L'hopital Rule: $$\lim\limits_{x\to 0} \frac{\ln(\frac{\sin x}{x})}{1-\cos x} = \lim\limits_{x\to 0} \frac{\frac{x}{\sin x}\cdot\frac{x\cos x - \sin x}{x^2}}{\sin x} = \lim\limits_{x\to 0}\frac{\frac{x\cos x - \sin x}{x\sin x}}{\sin x}$$

This is where I got stuck.
If I'm not mistaken the limit is $-\frac{1}{3}$ so the orginial one is $e^{-\frac{1}{3}}$

What should I do different (Or what's is wrong with my calculation?)

share|cite|improve this question
Have you tried applying the rule again? – Najib Idrissi Aug 8 '14 at 15:40
up vote 6 down vote accepted

After rearranging the quotient a bit we can apply L'hopitals rules $2$ more times to get the answer:



share|cite|improve this answer
Thanks, I should have just continue and not give up :) – Elimination Aug 8 '14 at 15:56
You're welcome. – user71352 Aug 8 '14 at 16:01

You can continue it as the following : $$\begin{align}\lim_{x\to 0}\frac{x\cos x-\sin x}{x\sin^2 x}&=\lim_{x\to 0}\frac{(x\cos x-\sin x)'}{(x\sin^2 x)'}\\&=\lim_{x\to 0}\frac{\color{red}{\cos x}-x\sin x\color{red}{-\cos x}}{\sin^2 x+2x\sin x\cos x}\\&=\lim_{x\to 0}\frac{-x}{\sin x+2x\cos x}\\&=\lim_{x\to 0}\frac{-1}{(\sin x/x)+2\cos x}\\&=\frac{-1}{1+2\cdot 1}.\end{align}$$

share|cite|improve this answer
Thank you @mathlove – Elimination Aug 8 '14 at 15:58
@Elimination: You are welcome. – mathlove Aug 8 '14 at 16:05

Alternative approach using Taylor series:

Using $\frac{\sin x}{x} = 1 - \frac{x^2}{6} + o(x^2)$ we get $\ln(\frac{\sin x}{x}) \sim_0 \ln(1-\frac{x^2}{6})$. This expression has the Taylor expansion $-\frac{x^2}{6}+o(x^2)$.

We can approximate the denominator by $1-\cos x=\frac{x^2}{2} + o(x^2)$.

Then we have: $\frac{\ln(\frac{\sin x}{x})}{1-\cos x} \sim_0 -\frac{x^2}{6} \frac{2}{x^2} = -\frac{1}{3}$.

This doesn't exactly answer your question, but hopefully it provides a little bit of insight. :)

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.